Estimating the value of offshore wind along the United States' Eastern Coast. (4th September 2018) - Mills, Andrew D; Millstein, Dev; Jeong, Seongeun; Lavin, Luke; Wiser, Ryan; Bolinger, Mark
Abstract: Offshore wind power deployment has been concentrated in Europe, and remains limited in other areas of the world. Among the many challenges to deployment is the need to understand the value that offshore wind provides within electricity markets. This article develops a rigorous method to assess the economic value of offshore wind along the eastern coastline of the United States, seeking improved understanding of how the value of offshore wind varies both geographically and over time, and what has driven that variation. The article uses historical (2007–2016) weather data at thousands of potential offshore wind sites, combined with historical wholesale electricity market outcomes and renewable energy certificate (REC) prices at hundreds of possible transmission interconnection points. We find that the average historical market value of offshore wind from 2007 to 2016—considering energy, capacity, and RECs—varies significantly by project location, from $40/MWh to more than $110/MWh, and is highest for sites off of New York, Connecticut, Rhode Island, and Massachusetts. As energy and REC prices have fallen in recent years, so too has the market value of offshore wind. The historical value of offshore wind is found to exceed that of onshore wind, due to offshore wind sites being located more favorably in terms of constrained pricing points, and also due to a more-favorable temporal profile of electricity production. Cost reductions that approximate those witnessed recently in Europe may be needed for offshore wind to offer a credible economic value proposition on a widespread basis in the United States.